2021
DOI: 10.1021/acs.jpcc.0c09957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymorphs and Local Defect Structures on NMR Parameters of Graphite Fluorides

Abstract: The role of local molecular structure on calculated 13 C and 19 F NMR chemical shifts for graphite fluoride materials was explored by using gauge-including projector augmented wave (GIPAW) computational methods for different periodic crystal polymorphs and density functional theory (DFT) gauge-including atomic orbital (GIAO) computational methods for individual graphite fluoride platelets, i.e., fluorinated graphene (FG). The impact of stacking sequences, d-spacing, and ring conformations on fully fluorinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 93 publications
2
19
0
Order By: Relevance
“…These results suggest that a new structural factor is responsible for these deshielding effects in graphite fluorides. Recently, we calculated 19 F and 13 C isotropic chemical shifts in (CF) n by DFT, 79 which considered crystal structures featuring different framework conformations (e.g., chair versus boat) and found that framework conformation alone can be responsible for nearly 50 ppm variability in 19 F isotropic chemical shifts. The 19 F and 13 C NMR isotropic nuclear shielding parameters of both chair and boat conformations were calculated for the ncrown ring perfluorocyclohexane (n-PFCH, for n = 1−4) series of molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results suggest that a new structural factor is responsible for these deshielding effects in graphite fluorides. Recently, we calculated 19 F and 13 C isotropic chemical shifts in (CF) n by DFT, 79 which considered crystal structures featuring different framework conformations (e.g., chair versus boat) and found that framework conformation alone can be responsible for nearly 50 ppm variability in 19 F isotropic chemical shifts. The 19 F and 13 C NMR isotropic nuclear shielding parameters of both chair and boat conformations were calculated for the ncrown ring perfluorocyclohexane (n-PFCH, for n = 1−4) series of molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is broadly consistent with our previous work calculating (CF) n properties by periodic boundary DFT and other results in the fluorographene literature. 79,99 The energy increase by inverting the core pattern ranges from 1.26 eV (bench) to 5.41 eV (zigzag), indicating that the configuration at the core/crown boundary has a significant effect on the overall energy. The ΔE total for randomized core arrangements ranges between 8.77 and 12.20 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations